2002
DOI: 10.1177/0256090920020304
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Size Effect on Stock Returns in India

Abstract: This paper reports the results of a study designed to examine if any firm-specific characteristics explain the cross-sectional variation in stock returns using Fama and Macbeth's methodology. It was found that size (measured by market capitalization), market leverage, price-to-book value, and earnings-to-price ratio were highly correlated with stock returns. While size and price-to-book-value were negatively correlated with stock returns, earningsto- price ratio and market leverage were found to be positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
4
16
0
1
Order By: Relevance
“…Since there is a negative impact between market size and stock returns, by 1% decrease in market size will increase the stock returns by 3.37%. The null hypothesis, H0 was rejected this negative significant impact between the market size and stock returns is aligned with past researcher, Mohanty (2002).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Since there is a negative impact between market size and stock returns, by 1% decrease in market size will increase the stock returns by 3.37%. The null hypothesis, H0 was rejected this negative significant impact between the market size and stock returns is aligned with past researcher, Mohanty (2002).…”
Section: Discussionsupporting
confidence: 77%
“…According to Mohanty (2002) who studied on firm-specific characteristics using Fama and Macbeth's approach, size of company and price to book value resulted to have an inverse relationship with https://doi. org/10.15405/epsbs.2020.12.05.56 Corresponding Author: Sahaida Laily Md Hashim Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 526 stock return, whereas the other variables, leverage and price-earnings ratio found to have a direct relationship with stock returns.…”
Section: Introductionmentioning
confidence: 99%
“…These results are not in accordance with the formulated hypothesis that size has a negative effect on stock returns. Mohanty (2002), in her research, found that size is positively related to stock return. She did not deny the opinion of Fama and French in their research in 1993, 1995, and 1996 that size is a proxy for several risk factors and premium size is the price of that risk.…”
Section: Resultsmentioning
confidence: 90%
“…Mohanty (2002) found size, market leverage, EIP ratio and price to BV ratio were related to returns and the size effect was most prominent. Connor & Sehgal (2001) studied the Fama and French three-factor model from 1989-1999.…”
Section: Determinants Ofstock Returnmentioning
confidence: 91%